Writing history and identity from war: the Battle of Osowiec in the Russian music and cinema - Luiz Cruz Aguilar, Sergio [UNESP]; Marques Caetano, Isabela (Universidade Estadual de Ponta Grossa (UEPG), 2023)
The current media resurgence of a World War I battle draws attention to the discourse employed in the development of Russian identity. The article analyzes two artistic works referring to the Battle of Fort Osowiec, the song by the Russian band Aria - Attack of the Dead, and the short film Attack of the Dead: Osowiec, in addition to interviews and secondary bibliography; with the objective of verifying how the song and the short film demonstrate the figure of strong characters, corroborating with the doctrine of a Strong Russia; and whether the works would be part of the current Russian government’s strategy of appropriating culture and symbolic objects from Russian history for political ends.
Escrevendo história e identidade a partir da guerra: a Batalha de Osowiec na música e no cinema russo
Keywords: First World War; Ideology; Media; Osowiec Battle; Russia